The Relevance of Accounting Information in a Stock Market Bubble: Evidence from Internet IPOs - BHATTACHARYA, Nilabhra (Institutional Knowledge at Singapore Management University, 2010)
Prior research shows that accounting information is relevant for stock valuation, failure prediction, performance evaluation, optimal contracting, and other decision-making contexts in relatively stable market settings. By contrast, accounting's role during stock market bubbles such as those involving a revolutionary emerging technology is the subject of considerable debate, and prominent market observers have alleged that outdated and flawed accounting practices contributed to the crash of the Internet-led high-tech bubble of the late 1990s. We address the issue of whether accounting data is informative in a stock market bubble by examining its failure prediction ability in the context of Internet IPOs, one of the most egregious and economically significant sectors of the high tech bubble. Our setting of young start-up firms is one in which there is relatively little room for managerial discretion with respect to accounting accruals; Internet firms' accounting earnings closely approximate operating cash flows. Yet in contrast to widespread criticisms of accounting and its alleged role in fueling the bubble, we find that accounting variables are highly informative for failure prediction; specifically, they are significant in explaining ex post realized Internet IPO failures. Using an existing IPO failure prediction methodology and two alternative definitions of innovative IPOs, we further show that ex ante, out-of-sample Internet IPO failure forecasts are associated with economically and statistically significant hedge returns. Our analyses suggest that the traditional financial reporting system could serve as an anchor during speculative bubbles.